Synthesis, Characterization and Anti-Inflammatory Activity of New 5-(3,4-Dichlorophenyl)-2-(aroylmethyl)thio-1,3,4-oxadiaxoles - Koksal, Meric; Bilge, S. Sirri; Bozkurt, Ayhan; Sahin, Z. Sibel; Isik, Samil; Erol, Dilek Demir (ECV-editio Cantor Verlag Medizin Naturwissenschaften, 2008)
Several 5-(3,4-dichlorophenvi)-2(aroylmethyl)thio-1,3,4-oxadiazoles were synthesized and characterized by elemental analyses, IR and nuclear magnetic resonance spectra. All compounds were evaluated for anti-inflammatory activity by determining their ability to provide protection against carregeenan-induced edema in rat paw. in addition, ulcerogenic activity was determined. The anti-inflammatory data scoring showed that compounds 5e, 5f and 5g, at the dose of 100 mg/kg, exhibited anti-inflammatory activity, which for compound 5f was comparable to that of the reference drug indometacin WAS 53-86-1).
Koksal, Meric/0000-0001-7662-9364; Sahin, Zarife Sibel/0000-0003-2745-7871;
Keywords: 1,3,4-Oxadiazoles; Anti-Inflammatory Activity; S-Alkylation; Synthesis; X-Ray Crystallography